1976
DOI: 10.1002/star.19760280302
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Pyrodextrinization of Corn Starch

Abstract: During pyrodextrinization of corn starch in the absence of any added catalyst under different experimental conditions, the changes of dextrinization might have two or threes stages and remarkable transformation would begin to occur at 190°C. At higher temperatures, many non‐carbohydrates are found. At lower temperatures, side chains of amylopectin‐like substances might be cleaved to produce the linear parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…The roasting of starch induces processes of depolymerisation, transglucosidation and repolymerisation inside a starch molecule (Leszczyński, ). A well‐known effect of these transformations is an increase in starch solubility in water and a decrease in its swelling power, both being the greater the higher is the roasting temperature (Ueno et al ., ). Analogous tendency was observed in the case of roasting potato starch without acid addition (native or retrograded) (Fig.…”
Section: Discussion Of Resultssupporting
confidence: 88%
“…The roasting of starch induces processes of depolymerisation, transglucosidation and repolymerisation inside a starch molecule (Leszczyński, ). A well‐known effect of these transformations is an increase in starch solubility in water and a decrease in its swelling power, both being the greater the higher is the roasting temperature (Ueno et al ., ). Analogous tendency was observed in the case of roasting potato starch without acid addition (native or retrograded) (Fig.…”
Section: Discussion Of Resultssupporting
confidence: 88%
“…This may be attributed to the differences in the starch composition particularly the amylose and amylopectin content, origin of the samples maturity ofthestarch granules, the typeofstarches viz.A, B or C ere. The results obtained in the present investigation are in good accordance with those of Ueno et al [6] and Kerr and Cleveland [16].…”
Section: Reducing Value (Ferricyanide Number) Of Dextrinssupporting
confidence: 93%
“…It was observed that the alkali lability value increased abruptly in early stages of dextrinization in case of jowar dextrins and then started to show a downward trend whereas there was a steep rise in the ALvalues in early stages in case of ragi, wheat and rice dextrins followed by levelling off in the later stages of pyrodextrinization. These results are in accord with those of Ueno et al [6], Sriuastaua et al [5] and Brimhall [l], particularly for the dextrins of ragi, wheat and rice starches. On the other hand, the results of alkali lability value for dextrins ofjowar starch are similar to that of Caesar and Cushing [17].…”
Section: Alkali Lability Value (Alv)supporting
confidence: 93%
See 1 more Smart Citation
“…C for 8 h in a DN400 oven (Yamato Scientific Co., Tokyo, Japan) to prepare the dry-heated flour. 14,15) The untreated flour was suspended in distilled water to produce a 30% (w/w) suspension. This suspension was poured on to a KZ-HP-1000-K hot-plate (Panasonic, Osaka, Japan), which had been heated at 160 C, and pressed with a heat block, which had also been preheated at 160 C, for 10 min with occasionally flipping.…”
Section: Methodsmentioning
confidence: 99%